Isolated vulvo-vaginal Crohn’s disease: case report of the rare entity - Ramji, Ashwath Narayan (International Surgery Journal, 2019)
The vulva is a rare site for extra-intestinal manifestation of Crohn’s disease, and is usually a late feature of severe, fulminant, unrelenting disease. These islands of granulomatous tissue in the female genitalia are considered “metastatic” deposits as they are separated from the intestinal lesions by healthy tissue. Very rarely, Crohn’s disease may manifest first in an extra-intestinal site, without any bowel lesions. In extremely rare cases, the genitalia is the site of isolated primary Crohn’s disease and serves as a harbinger for bowel lesions.